New learning styles models in adaptive educational process - Nidal A.M Jabari (Universitas Negeri Malang, 2020)
Abstract: This paper presented a new method in learning styles. This study focused on the learning styles studied by a group of researchers and obtained an insight into the most important styles. Through these styles, new learning styles have been formulated to give a broader base for researchers in the field of smart education to build educational systems that are able to deliver the educational subject to students better and faster. Key Words: style, smart, model, learner, visual Abstrak: Studi ini menyajikan metode baru dalam gaya belajar. Studi berfokus pada gaya belajar yang dipelajari oleh sekelompok peneliti dan memperoleh wawasan tentang gaya belajar yang paling penting. Melalui gaya-gaya tersebut, gaya belajar baru telah dirumuskan untuk memberikan dasar yang lebih luas bagi para peneliti di bidang pendidikan cerdas untuk membangun sistem pendidikan yang mampu memberikan pelajaran pendidikan kepada siswa dengan lebih baik dan cepat. Kata kunci: gaya, cerdas, model, pebelajar, visual